The Effect of the Think Talk Write (TTW) Learning Model on the Ability to Write Short Stories in Grade VII Middle School Students at Cenderamata, Medan City - Simangunsong, Ribka Mastiur; Simanungkalit, Elisa Putri Ayu; Matondang, Yohana Evaulina; Madina, Madina (Lembaga Riset Ilmiah, 2023)
The learning model is a whole series of presentations of teaching material which includes all aspects before and after learning by the teacher as well as all related facilities that are used directly or indirectly in the teaching and learning process, and in this study using the think talk write (TTW) learning model. Think Talk Write (TTW) is a learning model that starts from the flow of thinking through reading material (listening, criticizing, and alternative solutions) then talking by conducting discussions, and presentations, and finally writing by making reports on the results of discussions and presentations. The location of research was conducted in class VII junior high school students at Panca Budi School, Medan City, using 2 classes as a sample the control class and the experimental class with 30 students and in this study used a descriptive method. The results of this study show that the sig (2-tailed) value is 0.007, which is smaller than 0.05. Therefore, there is a significant difference between